A Novel Trajectory for a Transpedicular Approach in the Treatment of a Highly Downward-Migrated Lumbar Herniation with a Full Endoscopic Technique - Jiang, Yi; Zuo, Rujun; Yuan, Shuai; Li, Jian; Liu, Chang; Zhang, Jiexun; Ma, Ming (Frontiers in Surgery, 2022)
Background: To evaluate the clinical outcome of full endoscopic discectomy using a novel trajectory via transpedicular approach. Method: Thirty-five patients were enrolled in this retrospective study between July 2014 and October 2019 in Beijing Haidian hospital. All patients were treated with full-endoscopic lumbar discectomy via transpedicular approach with an oblique trajectory. The imaging parameters, including pedicle height and angle of trajectory, were recorded. The preoperative and post-operative clinical data were collected for statistical analysis. Results: All patients underwent successful surgery without severe complications. We compared the visual analogue scale and Oswestry disability index scores before and after surgery. The differences were statistically significant (P < 0.05). According to the modified Macnab criteria, the good-to-excellent rate was 85.7% at the last follow-up. The average angle of trajectory in sagittal and coronal planes were 34.5°±2.9° and 47.1°±5.0°, respectively. Conclusion: The new trajectory of the transpedicular approach with full endoscopic technique for extremely downward-migrated disc herniation showed excellent results in a small sample study. A precise surgical plan is required, comprising measurements of the pedicle height and angle of the bone tunnel.